THEY ARE SHAPING THE SUSTAINABLE DEVELOPMENT OF THE NATIONAL ECONOMY BASED ON INCLUSIVENESS - IRTYSHCHEVA, Inna; KRAMARENKO, Iryna; ZAVGORODNIY, Konstantin (Herald of Khmelnytskyi National University. Economic sciences, 2023)
A characteristic feature of the last century was humanity’s desire to ensure economic and technological development, which was considered the basis for achieving well-being and improving the standard of living. However, this progress was accompanied by using natural resources and environmental pollution, and the economy, environment, and social institutions functioned in isolation from each other. Global environmental problems, hunger, impoverishment of a large part of the population, moral degradation, and other challenges that the world faced at the beginning of the 21st century prompted the progressive international community and non-governmental organizations to start a new approach - the concept of sustainable development. This concept, which arose as a continuation of V. Vernadskyi’s concept of the noosphere, envisages the coordinated development of the economy, ecology, and social sphere to ensure the quality of people’s lives, the preservation of the environment, and social progress. The purpose of the article is to discuss the process of forming the sustainable development of the national economy based on inclusiveness. The words "sustainable" and "inclusive" have been combined into the term "sustainable, inclusive development", which reflects an attempt to combine two essential aspects of development: environmental sustainability and social inclusion. It has been determined that sustainable development is defined as development that meets the current needs of people without impairing the ability of future generations to meet their own needs. Accordingly, it is designed to balance economic, social, and ecological aspects of development, ensuring the preservation of natural resources and environmental protection. An assessment of Ukraine’s sustainable, inclusive development was carried out, during which it was determined that the term "sustainable inclusive development" reflects an attempt to combine two essential aspects of development: environmental sustainability and social inclusion. Such development reflects the importance of ensuring the harmonious development of society, which considers both the needs of current generations and the needs of future generations, as well as the inclusion of all members of society. The main principles of sustainable, inclusive development are defined: as non-discrimination, equal opportunities, and access to education, health care, and social services.